Self-reported prevalence of recurrent aphthous stomatitis among UiTM dental students / Wan Nur Hazirah Wan Ahmad Kamil ... [et al.] - Wan Ahmad Kamil, Wan Nur Hazirah; Amirham, Ilmi Qayyim; Omar, Muhammad Aniq Hakim; Zainal, Mukarramah (Faculty of Dentistry, Universiti Teknologi MARA, 2022)
Recurrent aphthous stomatitis (RAS) is a common mucosal disease characterized by multiple recurrent, small, round, or oval ulcers with circumscribed margins, erythematous haloes, and yellow grey base. Although the exact etiology is unknown, various factors can trigger RAS development. Objectives: This study aims to determine the prevalence of self-reported RAS and to evaluate the associated risk factors of RAS among dental students. Material and methods: A set of validated questionnaires was distributed among the dental students in the Faculty of Dentistry, UiTM. The questionnaire comprises socio-demographic characteristics, nature of ulcers, risk factors, and treatment modalities. Data obtained from the questionnaire were analyzed using Chisquare statistical test SPSS version 27. Results: A total of 299 dental students participated in the questionnaire survey. The prevalence of RAS among dental students was 90.3 %. There was no significant relationship between the socio-demographic background of participants with self-reported RAS. The most common site affected was the buccal mucosa 64.1%, followed by the lips 55.2%. Risk factors frequently associated with RAS are injury (trauma) and stress 47.8% and 28.1%, respectively. Most dental students (69.3%) do not get any treatment to treat their ulcers, and only 1.5% seek treatment from the dentist. Conclusions: This study highlights the high prevalence of self-reported RAS among dental students and common risk factors reported associated with the occurrence of RAS. Therefore, this data assists the clinician in identifying common associated risk factors of RAS and subsequently improve management and efficient therapeutics.